2011
DOI: 10.2298/jas1101055a
|View full text |Cite
|
Sign up to set email alerts
|

Logit analysis of socio-economic factors influencing people to become fishermen in the central region of Ghana

Abstract: This study analyzes the socio-economic factors that influence people’s decision to become fishermen in the central region of Ghana. Using a well structured interview schedule, a random sample of 98 people from Elmina in the central region of Ghana was selected for the study. Results from the descriptive statistics analysis of respondents identified fishing as a family business, minimum skills requirement and ready market for fish demand as factors that motivated majority of the people into fishing. Lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
2
6
1
Order By: Relevance
“…The small-scale fishing age in the West coast coastal area of Barru district has no significant effect on the decision of fishermen in selecting fishing gears and outboard engine power. This is in contrast to the findings by Acquah and Abunyuwah (2011) finding that the decision of the community to be a fisherman in the central Elmina Region of ghana that the respondent age, marital status and monthly income variables have no significant effect.…”
Section: Fishing Gear Outboard Engine Power -------------------------contrasting
confidence: 99%
See 2 more Smart Citations
“…The small-scale fishing age in the West coast coastal area of Barru district has no significant effect on the decision of fishermen in selecting fishing gears and outboard engine power. This is in contrast to the findings by Acquah and Abunyuwah (2011) finding that the decision of the community to be a fisherman in the central Elmina Region of ghana that the respondent age, marital status and monthly income variables have no significant effect.…”
Section: Fishing Gear Outboard Engine Power -------------------------contrasting
confidence: 99%
“…Variable of fishermen's age has not significant effect on the fishermen decisions in selecting fishing gears. A similar fishermen decision has been reported in Elmina Ghana (Acquah and Abunyuwah, 2011). Another case by Sudarmo et al (2015) finding found that fishing seasons, fuel use, ice availability and equipment significantly affected the development of fishing operations using arad nets in Tegal district while the size of fishing gear, clean water use and crew did not significantly affect.…”
Section: Fishing Gear Outboard Engine Power -------------------------supporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, a resident over the age of 40 was 1.829 times more likely to pay than a resident under the age of 40. A previous study conducted by (Acquah and Abunyuwah, 2011) in Ghana, also obtained a similar finding. Finally, when all other characteristics were held constant, the results revealed that a resident with a diploma was the most likely to pay (5.089) compared to others.…”
Section: Results From Tablesupporting
confidence: 82%
“…However, to the best of the researcher's knowledge, the emphasis has mainly been on access to credit by: vegetable growers, farmers (rice farmers and cocoa farmers) and Fishermen (see for example Denkyirah et al, 2016;Adams, 2015;Abunyuwah et al, 2013;Acquah & Abunyuwah, 2011;Ackah & Vuvor, 2011;Avortri et al, 2013;Akudugu et al, 2009). The following researchers have made enormous contributions in the field pertaining to access to credit by SMES (small and medium scale enterprises) in Ghana but not on study specific such as traders, farmers and fishermen's etc.…”
Section: Introductionmentioning
confidence: 99%